Pengaruh Pemahaman Budaya Lokal dan Pengoptimalan Kolaborasi Dengan Stakeholder Terhadap Peningkatan Kinerja Personil Polair Bengkulu dalam Rangka Penanganan Konflik Sosial : Penangkapan Ikan Menggunakan Peralatan Modern - Enggarsah Alimbaldi (CV RIFAINSTITUT, 2025)
This study aims to analyze the influence of local cultural understanding and the optimization of stakeholder collaboration on improving the performance of the Polair (Water Police) personnel in Bengkulu in addressing social conflicts related to the use of modern fishing equipment. A quantitative method was employed using a survey of 63 personnel from the Sub-directorates of Law Enforcement and Patrol at Ditpolair Polda Bengkulu. The collected data were analyzed using SPSS with multiple linear regression techniques. The results indicate that both local cultural understanding and stakeholder collaboration significantly and positively affect personnel performance. This study emphasizes the need for cultural awareness training and enhanced stakeholder coordination as key strategies for effective conflict resolution in coastal law enforcement.